Firm heterogeneity in services trade: Micro‐level evidence from eight OECD countries. (3rd October 2020) - Benz, Sebastian; Rouzet, Dorothée; Spinelli, Francesca
Abstract: This paper shows that smaller and less productive firms, as well as first‐time exporters, are overproportionally affected by services trade barriers using micro‐data from Belgium, Finland, Germany, Italy, Japan, Sweden, the United Kingdom and the United States. For these firms, both the propensity to export and export volumes to less restrictive destinations are significantly higher than to more restrictive destinations. In contrast, policy barriers measured by the OECD Services Trade Restrictiveness Index (STRI) do not affect export decisions of the largest, most productive and experience services firms. The pattern holds for two major modes of supply, cross‐border services exports and foreign affiliate sales of services firms. The findings are consistent with firm sorting mechanisms in trade models with heterogeneous firms and hysteresis of export participation in the presence of sunk export costs.